Implementasi Supervisi Akademik oleh Pengawas Dalam 8 Dimensi Pembelajaran Bertema Kearifan Lokal dan Kewirausahaan di SMP IT Darul Qur`an Sela Kecamatan Bungoro Kabupaten Pangkajene dan Kepulauan - Kartini Kartini; Rego Devilla; Erni Rismawanty (QISTINA: Jurnal Multidisiplin Indonesia, 2026)
This study aims to describe the implementation of academic supervision conducted by school supervisors within eight learning dimensions themed on local wisdom and entrepreneurship at SMP IT Darul Qur’an Sela, to identify the constraints encountered in its implementation, and to analyze the influence of academic supervision on improving the quality of learning integrated with local wisdom and entrepreneurship. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of school supervisors, the principal, and teachers. Data were collected through in-depth interviews, classroom observations, and documentation studies. Data analysis was carried out through data reduction, data display, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation. The findings indicate that academic supervision has been implemented in a planned and systematic manner through the stages of planning, implementation, and post-observation. However, its implementation remains predominantly administrative and has not optimally encouraged deep learning or the integration of local wisdom and entrepreneurship. The main constraints include limited training opportunities, a lack of contextual teaching materials, budget limitations, and insufficient continuous mentoring. Academic supervision has had an initial positive impact on teachers’ administrative discipline and students’ participation in group discussions, but it has not yet resulted in a significant and sustainable improvement in overall learning quality.